A formal perspective to modelling electronic commerce transactions - Ehikioya, Sylvanus A. (Revista Colombiana de Computación, 2001)
Many models of e-commerce applications use informal approaches and human intuition although their underlying data model is sound. Consequently, most of the designs contain inconsistencies and some hidden brittle spots that do not manifest until the applications are used. In addition, informal design approaches leave the determination of the correctness of system designs to the intuition of the designers. Informal design approaches do not provide the degree of correctness and reliability required for e- commerce transactions. Keywords: Formal methods, e-commerce, Z.